Distribution and abundance of hematophagous flies (Glossinidae, Stomoxys, and Tabanidae) in two national parks of Gabon - Bitome Essono Paul Yannick; Dechaume-Moncharmont François-Xavier; Mavoungou Jacques; Obiang Mba Régis; Duvallet Gérard; Bretagnolle François (Parasite, 2015)
In order to minimize risks of pathogen transmission with the development of ecotourism in Gabon, a seasonal inventory has been performed in five contrasted biotopes in Ivindo (INP) and Moukalaba-Doudou (MDNP) National Parks. A total of 10,033 hematophagous flies were captured. The Glossinidae, with six different species identified, was the most abundant group and constitutes about 60% of the captured flies compared to the Stomoxys (6 species also identified) and Tabanidae with 28% and 12%, respectively. The Glossinidae showed a higher rate of capture in primary forest and in research camps. In INP, the Stomoxys showed a higher rate of capture in secondary forest and at village borders, whereas in MDNP the Stomoxys were captured more in the savannah area. Thus, each fly group seemed to reach maximum abundance in different habitats. The Glossinidae were more abundant in primary forest and near research camps while Stomoxys were more abundant in secondary forest and savannah. The Tabanidae did not show a clear habitat preference.